The effects of various sources and levels of supplemental vitamin D3 on growth performance and serum 25(OH)D3 of young pigs - Flohr, Joshua Richard (Kansas State University, 2013)
Seven experiments using a total of 3,251 preweaned pigs, nursery pigs, and sows were used to determine the effects of: 1) supplemental vitamin D[subscript]3 on suckling and nursery pig growth, and maternal performance, and 2) high sulfate water, dietary zeolite and humic substance on nursery pig performance. Also, a web-based survey was developed to question pork producers and advisors of the swine industry on their knowledge of feed efficiency. Experiment 1 tested an oral dose of either; none, 40,000 or 80,000 IU vitamin D[subscript]3 given to pigs 24 to 48 h after farrowing. No differences in growth performance or bone mineralization were observed, but vitamin D[subscript]3 supplementation increased serum 25(OH)D[subscript]3 on d 10, 20, and 30, but returned to control values by d 52. Experiments 2 and 3 evaluated an oral dose of vitamin D[subscript]3 to pigs just before weaning, as well as added D[subscript]3 in nursery diets and in drinking water. There were no effects on growth performance; however, serum 25(OH)D[subscript]3 increased with all sources of vitamin D[subscript]3 supplementation. Experiment 4 evaluated if pigs had a preference to 1 of 3 dietary concentrations of vitamin D[subscript]3. Pigs ate less feed from diets containing very high levels of vitamin D[subscript]3 compared to commonly supplemented levels. Experiment 5 evaluated 3 levels of vitamin D[subscript]3 in sow diets. There were no effects on sow productivity, subsequent pig performance, or piglet bone ash content. However, increasing vitamin D[subscript]3 increased sow serum 25(OH)D[subscript]3, milk vitamin D, and pig serum 25(OH)D[subscript]3. Experiment 6 and 7 evaluated the effects of dietary zeolite and humic substances in nursery pigs drinking high sulfate water. Ultimately, pigs drinking high sulfate water had increased fecal moisture content and decreased growth performance, and feed additives evaluated were ineffective in ameliorating these negative effects. Finally, data collected from the feed efficiency survey suggest that there are knowledge gaps about practices that effect feed efficiency. Results from this survey will help extension educators better target specific industry segments with current information and provide more specific areas of future research where lack of information has been identified.
Keywords: Vitamin D; Feed efficiency survey; Vitamin D3; Sulfate water; Sows; Nursery pigs; Animal Sciences (0475)